Consumer Innovativeness and Consumer Engagement: User Motivation As a Mediator - Tian, Zemin; Lu, Mengyuan (Social behavior and personality, 2022)
Widely used mobile tourism applications have become a necessary tool for tourists, but few empirical researchers have examined the factors that influence consumer engagement with these applications. In this study we focused mainly on how consumer innovativeness and user motivation influence consumer engagement. We collected data online from 468 participants, and used structural equation modeling to analyze the data. Findings show that consumer innovativeness was positively associated with utilitarian, hedonic, and social user motivations, each of which was positively associated with consumer engagement. In addition, user motivation mediated the consumer innovativeness-consumer engagement relationship.